2018
DOI: 10.1055/a-0603-3792
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between the Brain Natriuretic Peptide (BNP) Level and Prognosis of Diabetic Nephropathy with Microalbuminuria: A 7-Year Follow-Up Study

Abstract: The aim of the study was to examine the relationship between the brain natriuretic peptide (BNP) level and prognosis of diabetic nephropathy. The subjects were 100 Japanese outpatients with type 2 diabetes mellitus with microalbuminuria. Associations between metabolic parameters at baseline, including BNP, and prognosis of diabetic nephropathy (progression of diabetic nephropathy, cardiovascular events, and death) were examined for 7 years. In Cox proportional hazard analysis, HbA1c, albumin-creatinine ratio (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Another study found that injection of BNP, which is mainly activated by furin [15,16,27], can lead to glomerular hyperfiltration in mice [28]. The association between BNP and microalbuminuria has also been observed in populations [9,29]. The underlined mechanisms need to be discussed to deepen our understanding of the role of furin in microalbuminuria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study found that injection of BNP, which is mainly activated by furin [15,16,27], can lead to glomerular hyperfiltration in mice [28]. The association between BNP and microalbuminuria has also been observed in populations [9,29]. The underlined mechanisms need to be discussed to deepen our understanding of the role of furin in microalbuminuria.…”
Section: Discussionmentioning
confidence: 99%
“…In-depth understanding of the mechanisms and risk factors of microalbuminuria is undoubted of great relevance for the prevention and management of this debilitating disorder and related complications, e.g., kidney and vascular diseases. Natriuretic peptide system has been involved in the pathogenesis of microalbuminuria [7][8][9][10] through shedding the endothelial glycocalyx [11,12], increasing vascular permeability [12], enhancing hydraulic pressure in the glomerular capillaries [13,14], and thereby resulting in increased excretion of albumin in the urine. As a key activator of the precursor of brain natriuretic peptide (BNP), one key component of natriuretic peptide system, furin may play a critical role in the natriuretic peptide system and thus participates in the pathogenesis of microalbuminuria [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies [ 22 , 23 ] found a positive correlation between NT-proBNP concentrations and the severity of proteinuria in patients with T2DM. Other studies [ 24 , 25 ] showed that NT-proBNP concentrations were negatively correlated with baseline eGFR and positively correlated with kidney function decline in patients with CKD.…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies have shown that DN cannot be effectively suppressed even if blood sugar and blood pressure are strictly controlled in diabetic patients. Indeed, about 33 % of diabetic patients still end up with end-stage renal disease [8]. Therefore, early diagnosis of diabetes and early treatment are of great significance for delaying the development of DN and improving life quality amongst diabetics.…”
Section: Discussionmentioning
confidence: 99%